The analysis of the use of satire in the daily show with Trevor Noah - Rahma, Sitti; Lubis, Syahron; Perangin-angin, Alemina (Universitas Islam Negeri Banda Aceh, 2023)
Various TV channels established with various talk shows stand out among other shows for presenting bitter facts in a very light-hearted way by commenting, satirizing, analyzing and criticizing in a very funny style.